การบริหารงานการฝึกอบรม : ศึกษาเฉพาะกรณีธนาคารแห่งประเทศไทย - วรรณวดี ฤทธารมย์ (จุฬาลงกรณ์มหาวิทยาลัย, 1980)
Presently all the organizations try to speed up their development of effective management and performance in order to reach aimed objectives. As is generally accepted whether such development will succeed or not depends on the human as the important factor. Prudent organizations try to keep highly productive employees and reduce less productive employees. There are many causes of less productive employees. The main ones are being lack of knowledge and skill, and wrong attitude towards the job. Ways to help to improve such weak points now and in the future can be obtained in different ways : 1. Formal Education 2. Training 3. Self-Development. While the employees are working, the organization must recognize the importance of training and try to introduce training schemes to the employees. Since the training means development and improvement of opinions, activities, knowledge and skills as well as to increase the standard of performance, it will help reach the goals set by the organization and their employees. This thesis studies about the principle, philosophy and process of the management training of the Bank of Thailand by method of documentary and field research. In order to help its employees they receive training in both management and performance to gain knowledge, understanding, skill and suitable attitudes useful in their work. The conclusion is that training management of the Bank of Thailand is a necessity and need of the organization and employees. However, the data of field research showed that the trainees were enthusiastic after completing training, but later lost their enthusiasm. We can see that only training can’t help develop long-run performance of the employees. The writer suggests that the Training Center of the Bank of Thailand have a follow-up and continuous training program and patternaly begin changing and developing its system through teaching Behavioral Science dealing with the fundamental knowledge of Organization Development and introducing it in the Bank of Thailand.